PERFORMANSI MOTOR BENSIN SEPEDA MOTOR SUZUKI SMASH 110 CC DENGAN BAHAN BAKAR CAMPURAN BENSIN DAN â€œCAP TIKUSâ€ - Mario Herlen Pajow; Hardi Gunawan; Tertius Viktor Yefta Ulaan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2012)
One solution in utilization of fossil fuel in a motorcycle with gasoline engine is mixing the gasoline with methanol. In this research, a test was conducted on a year 2003 edition Suzuki Smash 110 cc motorcycle to measure is fuel consumption using the methanol gasoline mixture. The methanol used in this research is a traditional Minahasa liquor which is called â€œCap Tikusâ€. The traditional liquor then mixed with gasoline with 5, 10, and 15% volume ratio.In this research, it is assumed that the contents of gasoline is octane (C8H18) and that â€œCap Tikusâ€ contains 65% methanol (CH3OH) and 35% water (H2O). From the calculations, it is obtained that upper heating values of the mixture fuel are 12.225; 11.775; 11.261; and 10.744 kkal/kg for 0, 5, 10, and 15% volume proportion of â€œCap Tikusâ€ respectively. From tests it is obtained that specific fuel consumption values 0,073; 0,076; 0,079; and 0,081kg/kWh for 0, 5, 10, and 15% of mixture.The calculated theorical power using the heating values of the fuel are 0,575; 0,525; 0,475; and 0,425 hp for the mixing fuel with 0, 5, 10, and 15% volume proportion of â€œCap Tikusâ€. The result showed that mixing gasoline with methanol up to 15% volume ratio is not increased the power of the engine.Keywords : Suzuki Smash Engine, Methanol, Fuel Consumption.